A Case of Steroid Resistant Minimal Change Disease Associated with Portal Vein Thrombosis Treated by Combined Immunosuppressive Agents - Hyo Jin Jung; Su Mi Lee; Seo Hee Rha; Seong Eun Kim; Young Ki Son; Ki Seung Kim; Won Suk An (Kosin Medical Journal, 2017)
Minimal change disease (MCD) is a common cause of nephrotic syndrome and relatively well responds with steroid treatment. However, nearly half of patients with MCD experience recurrence of nephrotic syndrome. Thromboembolic events including renal vein thrombosis may occur in patients with MCD, but portal vein thrombosis rarely occurs. We experienced a case of frequent relapse/steroid dependent MCD with nephrotic syndrome progressed to steroid resistance associated with portal vein thrombosis. This patient showed complete remission of MCD and resolution of portal vein thrombosis after treatment with corticosteroid, cyclosporine, mycophenolate mofetil, and anticoagulant.